Self Disclosure SEVENTEEN CARAT Melalui Fan Account di Media Sosial Twitter “X” - Amanda Diva; Yudiana Indriastuti (Journal Education Innovation (JEI), 2024)
The emergence of social media can be anytime and anywhere sharing anything about personal things, as well as feelings and activities in the media. Twitter social media "X" can make it easier for fans to get information about their idoka, this activity is carried out by fans through fan accounts. The fan account that was originally used to carry out fangirling activities then over time not only conveyed information about their idols, but also personal anxiety or self-openness because the CARAT fan account users did not know each other in the real world.The purpose of this study is to find out how self-disclosure is carried out by CARAT who is a fan of Kpop boy band SEVENTEEN through a fan account on social media Twitter "X". This study used qualitative research methods using a descriptive approach. Data was collected through in-depth interviews, documentation, and observation. The results showed that each individual has their own driving factors according to the experience felt when interacting on their fan account to do self-disclosure. Self-disclosure has both positive and negative impacts. The positive impact felt by informants is in the form of creating good relationships between fan account users and being able to realize many things about themselves by looking at other people's responses. The negative impact is abandonment and rejection. This finding provides an idea of how Kpop fans namely CARAT use their fan accounts not only to share information but they use it as a forum for self-disclosure.